Investigating farm-level exit decisions and exit rates in commercial agriculture in South Africa, an agent-based approach - Cloete, Johanna Cecilia (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.